2022
DOI: 10.1021/acscatal.2c02630
|View full text |Cite
|
Sign up to set email alerts
|

Following Adsorbed Intermediates on a Platinum Gas Diffusion Electrode in H3PO3-Containing Electrolytes Using In Situ X-ray Absorption Spectroscopy

Abstract: One of the challenges of high-temperature polymer electrolyte membrane fuel cells is the poisoning of the Pt catalyst with H3PO4. H3PO4 is imbibed into the routinely used polybenzimidazole-based membranes, which facilitate proton conductivity in the temperature range of 120–200 °C. However, when leached out of the membrane by water produced during operation, H3PO4 adsorbs on the Pt catalyst surface, blocking the active sites and hindering the oxygen reduction reaction (ORR). The reduction of H3PO4 to H3PO3, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This difference is in line with the possibility of H 3 PO 3 oxidation by H 2 O (as discussed previously and summarized by eq ), due to the higher H 2 O:H 3 PO 3 molar ratio in 1 mol dm –3 compared to 5 mol dm –3 H 3 PO 3 solution. Furthermore, the averaged OCP values for Pt|1 mol dm –3 H 3 PO 3 and Pt|5 mol dm –3 H 3 PO 3 in this study are +0.47 and +0.41 V vs RHE, respectively, which are similar to the potential at which the majority of adsorbed species on Pt correspond to H 3 PO 3 in its pyramidal form (at +0.4 V), as reported by Gomes et al However, according to our findings, it seems that the notion of Pt “equilibrium surface coverage” by H 3 PO 3 previously reported by Gomes et al has not been correctly attributed. The oxidation of H 3 PO 3 to H 3 PO 4 on Pt, likely through the reaction of highly reactive pyramidal H 3 PO 3 with H 2 O via eq , as previously discussed, provides a new interpretation of the H 3 PO 3 adsorption on Pt: the equilibrium coverages are to be reconsidered as steady-state ones, i.e., following the oxidation of H 3 PO 3 on Pt.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This difference is in line with the possibility of H 3 PO 3 oxidation by H 2 O (as discussed previously and summarized by eq ), due to the higher H 2 O:H 3 PO 3 molar ratio in 1 mol dm –3 compared to 5 mol dm –3 H 3 PO 3 solution. Furthermore, the averaged OCP values for Pt|1 mol dm –3 H 3 PO 3 and Pt|5 mol dm –3 H 3 PO 3 in this study are +0.47 and +0.41 V vs RHE, respectively, which are similar to the potential at which the majority of adsorbed species on Pt correspond to H 3 PO 3 in its pyramidal form (at +0.4 V), as reported by Gomes et al However, according to our findings, it seems that the notion of Pt “equilibrium surface coverage” by H 3 PO 3 previously reported by Gomes et al has not been correctly attributed. The oxidation of H 3 PO 3 to H 3 PO 4 on Pt, likely through the reaction of highly reactive pyramidal H 3 PO 3 with H 2 O via eq , as previously discussed, provides a new interpretation of the H 3 PO 3 adsorption on Pt: the equilibrium coverages are to be reconsidered as steady-state ones, i.e., following the oxidation of H 3 PO 3 on Pt.…”
Section: Resultssupporting
confidence: 89%
“…However, the low oxidation current density at Pt suggests that the Pt surface is easily blocked/poisoned by adsorbed H 3 PO 3 or its oxidation products, which is in agreement with the increasing OCP value over time in the previously discussed electrochemical experiment with the GDE, in Figure E and Figure S4 as well as previous observation. , Furthermore, for both planar metal electrodes, the oxidation of H 3 PO 3 stops once the metallic surface is covered by higher oxides (shown by gray dashed lines in Figure ), indicating that metallic presence is favorable toward the oxidation of H 3 PO 3 . Previous investigations have also suggested that H 3 PO 3 adsorb on top of Pt within the potential range of 0.0 V to +0.5 V vs RHE, where metallic Pt is accessible from the electrolyte phase . This adsorption occurs in its pyramidal form through a P–Pt interaction.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…36−38 The adsorption of H 3 P (III) O 3 on a Pt surface at ambient temperature has already been proven electrochemically 39 and indicated spectroscopically through the combination of X-ray absorption spectroscopy at P L 3 -edge and density functional theory. 40 Hence, P K-edge XANES measurements on these compounds will be beneficial (and a prerequisite) for future operando studies of these systems. Furthermore, P K-edge XANES was also performed on aqueous phosphoric acid (H 3 PO 4 ), aqueous phosphorus acid (H 3 PO 3 ), and their mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In the extended X-ray absorption fine structure (EXAFS) region in k-space (Figure 2b), the oscillations of the ex situ measurement are slightly modified before the ECA and are even stronger after the ECA. This feature could be related to adsorbates at the electrode/electrolyte interface 24 and surface restructuring induced by the ECA, which modifies the local coordination environment. The average first-shell Pt−Pt coordination number (N Pt−Pt ) and the average Pt−Pt bond lengths (R Pt−Pt ) were determined by fitting the filtered Fouriertransformed EXAFS spectra in the R-space shown in Figure 2c (fitting details are given in the Supporting Information S6).…”
mentioning
confidence: 99%